Rouge - Kirshenbaum, Richard, 1961- (St. Martin's Press, 2019)
This fast-paced novel examines the lives, loves, and sacrifices of the visionaries who invented the modern cosmetics industry: Josiah Herzenstein, born in a Polish Jewish Shtlel, the entrepreneur who transforms herself into a global style icon and the richest woman in the world, Josephine Herz; Constance Gardiner, her rival, the ultimate society woman who invents the door-to-door business and its female workforce but whose deepest secret threatens everything; CeeCee Lopez, the bi-racial beauty and founder of the first African American woman's hair relaxer business, who overcomes prejudice and heartbreak to become her community's first female millionaire. The cast of characters is rounded out by Mickey Heron, a dashing, sexy ladies' man whose cosmetics business is founded in a Hollywood brothel. All are bound in a struggle to be number one, doing anything to get there- including murder.